Cardiovascular Disease (CVD) and Genomics Imbalance to Risk Oxidative Stress Following Environmental Stress: Molecular Vitality for Prediction and Prevention - Aleq M. Jaffery; Yoon Ju Lee; Diane E. Heck; Hong Duck Kim (Current Aspects in Pharmaceutical Research and Development Vol. 7, 2022)
Cardiovascular disease (CVD) is one of high burdens accompanied with health cost and intensive care by personalized prevention platforms including various drug options. It develops differently following risk factors (i.e., smoking, high fat diet, alcohol, stressor, and sedentary behavior) which may cause blood flow and heart dysfunction such as microvascular dysfunction (eg. Artery diseases), myocardial infarction (MI), arrhythmias, angina, and atherosclerosis. There are still bias CVD pathogenesis and endpoint variation between plaque formation and risk factors derived from intrinsic (or genetic risk) or extrinsic (or environmental risk). In previous studies Lipoprotein is predominantly affected to blood flow and plaque formation in previous studies. In addition, there is compelling evidence to emphasize several risk factors in patient history such as a high blood pressure, vascular damage to heart value, and metabolic disorder could be associated with diets which may contribute to developing heart failure and stroke in clinic and animal models like apoE transgenic animals. In this report, we review molecular tools (i.e., multidimensional Omics or systemic biology equipped with various detection module like genomics, proteomics, metabolomics, and pharmacogenomics, etc) for support early prediction and prevention patient from environmental risks and conduct systematic health care align with surveillance and monitoring including molecular sensitivity and validation combined with traditional imaging system in therapeutic and prevention options to reduce drug insensitivity upon individual genetic diversity which may observed in several metabolic symptoms in the aging population Using Genomics, we visualized patient’s genomics variation or polymorphism by accessing DNA sequences for a comparison to those unaffected. Those output is worth determining what genes are mutated and who are more at risk due to their genetic makeup. Furthermore, proteomics will enhance the study of targeting proteins, including their locations, structures, and functions to better regulate the cardiopathy or cardiac malfunction. Metabolomics is the Omics tool for studying drug efficacy and metabolism that are involved in the transmission of cardiopathies. Moreover, Metabolite’s identification can enhance one’s knowledge of metabolic pathways to high fat diets, and how certain environmental factors and genetic factors surrounding blood flow and altered molecular networks in plaque formation can affect cardiac dysfunction and its regulatory pathways. Finally, pharmacogenomics will help determine effective drugs on a more personalized based approach to ensure that anyone with any form of metabolic disorder or hypertension has a predisposition chronic diseases pattern. This will specifically enlighten the value of systemic detection using molecular tools by integrating to target, Lipoproteins, the correct focus in early cardiomyopathy process and validation in various therapeutic endpoints to ensure quality outcomes.